2011
DOI: 10.1186/1752-4458-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from case studies of integrating mental health into primary health care in South Africa and Uganda

Abstract: BackgroundWhile decentralized and integrated primary mental healthcare forms the core of mental health policies in many low- and middle-income countries (LMICs), implementation remains a challenge. The aim of this study was to understand how the use of a common implementation framework could assist in the integration of mental health into primary healthcare in Ugandan and South African district demonstration sites. The foci and form of the services developed differed across the country sites depending on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 23 publications
3
107
0
1
Order By: Relevance
“…These benefits are that if mental health services are integrated into general health care, the burden of mental health is reduced in the community; people are treated holistically; the treatment gap is reduced; access to mental health services is enhanced; there is respect for human dignity and good health outcomes. 22 Petersen et al 23 recommended that district management authorities should be educated on what integration entails so that they develop the political will-power to strengthen mental health services provision in PHC clinics. They also supported the implementation framework of task-shifting, where psychiatric trained nurses from the hospital are deployed to work in PHC clinics in order to improve mental health care services.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…These benefits are that if mental health services are integrated into general health care, the burden of mental health is reduced in the community; people are treated holistically; the treatment gap is reduced; access to mental health services is enhanced; there is respect for human dignity and good health outcomes. 22 Petersen et al 23 recommended that district management authorities should be educated on what integration entails so that they develop the political will-power to strengthen mental health services provision in PHC clinics. They also supported the implementation framework of task-shifting, where psychiatric trained nurses from the hospital are deployed to work in PHC clinics in order to improve mental health care services.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They also supported the implementation framework of task-shifting, where psychiatric trained nurses from the hospital are deployed to work in PHC clinics in order to improve mental health care services. 23 …”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this study, 98% (49) of the participants (registered nurse) indicated that they had never been supervised in the area of mental health to enable them to implement the policy. According to Dreyer, [24] there is a trend in policy implementation of ignoring the policy implementer, and it is common to observe a gap between what is planned and what actually occurs as a result of a policy.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…[1] As a result, programme implementers could choose one policy to implement in this case, while ignoring others which, in this case, are the mental health policy. [24] This study indicated that training of general health care workers would equip them with the skills needed to manage cases of mental illness appropriately. Accordingly, the detection and management of mental health problems should be improved so that people will be more willing to access care, care will be brought closer to the communities, there will be more human resources and there will likely be fewer patients.…”
Section: Based On Gilson Et Al'smentioning
confidence: 99%
“…In resource-poor settings, the model focuses on improving the recognition and treatment of people with mental illnesses within primary health care clinics, alongside the treatment of more complicated cases at specialised centres. Other approaches include community collaborative models that feature multi-sectoral collaborations between health services, user and family groups, NGOs and multi-sectoral collaborative forums that draw on participation from social welfare sectors, as well as the general community (Petersen & Ssebunnya, 2011). Community collaborative approaches rely on task shifting and sharing strategies, which increases access to treatment for selected priority illnesses, such as psychotic disorders, or common mental disorders (CMD).…”
Section: Background: a Policy For Primary Mental Health Care In Southmentioning
confidence: 99%